Rückenwind Evaluationsstudie eines Förderprogrammes der AK Tirol für Junge - Speyer, Anja; Torggler, Jutta; Staubmann, Helmut (innsbruck university press, 2017)
" ""Rückenwind"", a project of the AK Tirol for Young, sets itself the goal to strengthen young people and adolescents for their future life. The focus was on how former participants assess the ""tailwind"" project, why they decide to participate in a project, what experiences they have in the project and to what extent they actually succeed in maintaining a tailwind by participating in the project and developing individual competences."